Pengaruh Motivasi dan Kompensasi terhadap Kinerja Karyawan : Studi pada Mebel Dahlia Kecamatan Kawali Kabupaten Ciamis (International Forum of Researchers and Lecturers, 2023)
The problems faced in this study include (1) How does motivation affect employee performance in Dahlia Furniture, Kawali District, Ciamis Regency? (2) How does compensation affect employee performance in Dahlia Furniture, Kawali District, Ciamis Regency? (3) How does motivation and compensation affect employee performance in Dahlia Furniture, Kawali District, Ciamis Regency? This study aims to study, know, and analyze (1) The influence of motivation on employee performance in Dahlia Furniture, Kawali District, Ciamis Regency. (2) The effect of compensation on employee performance in Dahlia Furniture, Kawali District, Ciamis Regency. (3) The effect of motivation and compensation on employee performance in Dahlia Furniture, Kawali District, Ciamis Regency. The method used in this study is explanatory survey, while the technical data analysis is validity test, reliability test, descriptive statistics, Inductive Statistical Analysis (Inferential) with Multiple Regression. The results of the study inform that (1) Motivation has a positive effect on employee performance in Dahlia Furniture, Kawali District, Ciamis Regency. This means that if motivation is increased, the performance of employees in Kawali District, Ciamis Regency will also increase. (2) Compensation has a positive effect on employee performance at Dahlia Furniture, Kawali District, Ciamis Regency. This means that if the compensation is increased, the performance of employees at Mebel Dahlia, Kawali District, Ciamis Regency will also increase. (3) Motivation and compensation have a positive effect on employee performance at Dahlia Furniture, Kawali District, Ciamis Regency. This means that if motivation and compensation are increased, then employee performance at Mebel Dahlia Kawali District, Ciamis Regency will also increase.